A microporous carbon-silicon composite negative electrode material and preparation method thereof, negative electrode sheet and secondary battery

By combining nitrolitin sulfonate with phenolic resin prepolymer and with graphitization reagents and low-carbon chain carbon sources, a microporous carbon-silicon composite anode material with interconnected carbon network structure and nanographitized carbon tape was prepared, which solved the problem of high low-temperature discharge resistance of existing materials and significantly improved the discharge performance.

CN117913230BActive Publication Date: 2025-04-08JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD

Patent Information

Application Number
CN202311733706.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2025-04-08
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

The existing microporous carbon-silicon composite anode materials have high discharge resistance and poor discharge performance at low temperatures, making it difficult to effectively solve the material expansion problem caused by the silicon volume effect.

Method used

The nitrated lignin sulfonate is combined with the phenolic resin prepolymer to form a nitrated lignin-polymer composite through secondary polymerization, and combined with graphitization reagents and low-carbon chain carbon sources to prepare a microporous carbon-silicon composite anode material with an interconnected carbon network structure and nanographitized carbon tape.

Benefits of technology

The low-temperature discharge resistance of the material is reduced, the discharge performance of the material is improved, and the lithium ion diffusion and electron transport are optimized through tight carbon-silicon bonding and improved conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117913230B_ABST
    Figure CN117913230B_ABST
Patent Text Reader

Abstract

The present invention provides the application of nitrated lignin sulfonate in the preparation of microporous carbon-silicon composite negative electrode materials. The present invention uses nitrated lignin sulfonate to prepare microporous carbon-silicon composite negative electrode materials, and also provides a silicon-carbon composite negative electrode material and a preparation method thereof. The present invention uses lignin-polymer interconnected composite carbonization to construct an interconnected carbon network structure, and forms nanographitized carbon ribbons inside the carbon network structure. On the one hand, the microphase separation between the two phases of lignin and phenolic resin polymer is hindered, so that the pore size of the obtained microporous carbon-silicon composite negative electrode material is concentrated in micropores within 2nm; on the other hand, the interconnected carbon network structure interconnects the pores of the nanocarbon material, and the silicon-carbon matrix is ​​more tightly bonded. The sufficient and interconnected channel characteristics are conducive to reducing the diffusion resistance of lithium ions, optimizing the electron transmission path, improving the electron transmission efficiency, and facilitating the lithium ions to enter the micropores and alloy with silicon to form a silicon-lithium phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of negative electrode materials for lithium-ion secondary batteries, and relates to the application of nitrated lignin sulfonate in the preparation of microporous carbon-silicon composite negative electrode materials, a microporous carbon-silicon composite negative electrode material and a preparation method thereof, a negative electrode pole piece, and a secondary battery, and in particular to a microporous carbon-silicon composite negative electrode material and a preparation method thereof, a negative electrode pole piece, and a secondary battery. Background Art

[0002] The development of high energy density lithium-ion secondary batteries is of great significance for promoting pure electric vehicles and alleviating the energy crisis. Silicon-based materials are recognized as the next generation of lithium-ion battery negative electrode materials because they have a theoretical capacity far higher than the current graphite negative electrode.

[0003] However, basic problems such as the serious volume effect of silicon during the charging and discharging process have seriously hindered the effective use of its advantages. The current better processing strategy is to form a large number of microporous carbon structures, use the pore space in the microporous carbon to deposit part of the silicon, and reserve a part of the space for the nano-silicon cycle process for the expansion of silicon, which causes the volume to increase. This reduces the expansion of the silicon-carbon negative electrode material and improves the cycle performance.

[0004] However, the result is that the bonding between silicon and microporous carbon in the microporous carbon structure is poor, resulting in a higher low-temperature discharge resistance of the silicon negative electrode material and a poor discharge performance of the silicon negative electrode material.

[0005] Therefore, how to find a more appropriate way to provide an effective method to solve the above-mentioned problems existing in the existing technology has become one of the urgent problems to be solved by many front-line researchers in the industry. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide an application of nitrated lignin sulfonate in the preparation of a microporous carbon-silicon composite negative electrode material, a microporous carbon-silicon composite negative electrode material and a preparation method thereof, a negative electrode sheet and a secondary battery. The multi-phase doped silicon-carbon negative electrode material provided by the present invention and its application in a secondary battery can reduce the low-temperature discharge resistance of the material and improve the discharge performance of the material.

[0007] The invention provides application of nitrated lignin sulfonate in preparing microporous carbon-silicon composite negative electrode material.

[0008] Preferably, the application also includes the application of combining nitrated lignin sulfonate and phenolic resin prepolymer in the preparation of microporous carbon-silicon composite negative electrode materials;

[0009] The combination of the nitrated lignin sulfonate and the phenolic resin prepolymer is specifically that the nitrated lignin sulfonate and the phenolic resin prepolymer are polymerized secondary to form a nitrated lignin-polymer composite;

[0010] The nitrated lignin-polymer composite has a chemically bonded interpenetrating network structure.

[0011] Preferably, the chemical bonding comprises chemical bonding between the hydroxyl groups of the nitrated lignin sulfonate and the aldehyde groups in the prepolymer;

[0012] In the nitrated lignin-polymer composite, the network structure of the nitrated lignin sulfonate and the network structure of the phenolic resin interpenetrate with each other to form an interpenetrating network structure;

[0013] The mass ratio of the added amount of nitrated lignin to the phenolic resin prepolymer is (0.002-0.08):1.

[0014] Preferably, the application also includes the application of nitrated lignin sulfonate, phenolic resin prepolymer and graphitization agent in the preparation of microporous carbon-silicon composite negative electrode material;

[0015] The graphitization agent includes metal oxalate and / or metal citrate;

[0016] The mass ratio of the graphitization agent to the nitrated lignin-polymer composite is (0.005-0.06):1.

[0017] Preferably, the application also includes the application of nitrated lignin sulfonate, phenolic resin prepolymer, graphitization agent and C1-C4 low carbon chain carbon source in the preparation of microporous carbon-silicon composite negative electrode material;

[0018] The C1-C4 low-carbon chain carbon source includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne and butyne;

[0019] The C1-C4 low-carbon chain carbon source is used to form a coating layer of a microporous carbon-silicon composite negative electrode material.

[0020] The application is specifically to reduce the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material and / or to improve the discharge performance of the microporous carbon-silicon composite negative electrode material.

[0021] Preferably, the micropores in the microporous carbon-silicon composite negative electrode material satisfy the following relationship:

[0022] 0.22≤MP 2- / MP all ≤0.58;

[0023] in,

[0024] MP 2- is the total volume of micropores per unit mass in the microporous carbon-silicon composite negative electrode material;

[0025] MPall It is the total volume of pores per unit mass of microporous carbon-silicon composite negative electrode material.

[0026] The present invention provides a microporous carbon-silicon composite negative electrode material, wherein the microporous carbon-silicon composite negative electrode material is prepared from nitrated lignin sulfonate, phenolic resin prepolymer, graphitization agent, silicon source and C1-C4 low-carbon chain carbon source;

[0027] The microporous carbon-silicon composite negative electrode material has a coating structure.

[0028] Preferably, the coating structure is specifically that the surface of the microporous carbon-silicon composite negative electrode material has a carbon coating layer;

[0029] The thickness of the carbon coating layer is 2-80 nm;

[0030] The specific surface area of ​​the microporous carbon-silicon composite negative electrode material is 0.75-8m 2 / g.

[0031] Preferably, the mass content of carbon in the microporous carbon-silicon composite negative electrode material is 15% to 65%;

[0032] The mass content of silicon in the microporous carbon-silicon composite negative electrode material is 15% to 65%;

[0033] The mass content of carbon and silicon in the microporous carbon-silicon composite negative electrode material is 80% to 99%;

[0034] The carbon main body of the microporous carbon-silicon composite negative electrode material is porous carbon and nanographitized carbon ribbon formed by carbonizing a nitrated lignin-polymer composite.

[0035] The present invention provides a method for preparing a microporous carbon-silicon composite negative electrode material, comprising the following steps:

[0036] 1) Prepolymerizing a phenol source, an aldehyde source and an acid catalyst, and then adding nitrated lignin sulfonate to perform secondary polymerization to obtain a nitrated lignin-polymer composite;

[0037] 2) Under vacuum conditions, the nitrated lignin-polymer composite obtained in the above step and the graphitization agent are heated, melted and mixed, and then carbonized under a protective atmosphere to obtain a nitrated lignin-polymer microporous carbon precursor;

[0038] 3) After acid washing, the nitrated lignin-polymer microporous carbon precursor obtained in the above step is introduced into a gaseous silicon source under vacuum conditions to perform silicon deposition to obtain a microporous carbon silicon matrix;

[0039] 4) Under the condition of a low-carbon chain carbon source of C1~C4, the microporous carbon silicon matrix obtained in the above steps is carbon-coated to obtain a microporous carbon silicon composite negative electrode material.

[0040] Preferably, the phenol source comprises one or more of phenol, nitrophenol, p-quinone, m-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol and naphthalene;

[0041] The aldehyde source includes one or more of formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde and furfural;

[0042] The acid catalyst includes p-toluenesulfonic acid.

[0043] Preferably, the amount of the phenol source and the aldehyde source, calculated as a phenol-aldehyde molar ratio, is 1:(1.5-4);

[0044] The temperature of the prepolymerization reaction is 35-70°C;

[0045] The prepolymerization reaction time is 0.3 to 2 hours;

[0046] The temperature of the secondary polymerization is 35-70°C;

[0047] The time of the secondary polymerization is 1 to 5 hours.

[0048] Preferably, the preparation process of the nitrated lignin sulfonate comprises the following steps:

[0049] After reacting the lignin sulfonate solution with nitric acid, alkali is added to obtain nitrated lignin;

[0050] The mass ratio of the lignin sulfonate to nitric acid is 1:(0.1-0.8);

[0051] The lignin sulfonate includes one or more of sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate and magnesium lignin sulfonate;

[0052] The reaction temperature is 30-80°C;

[0053] The reaction time is 1 to 8 hours;

[0054] The adding of alkali specifically includes adding alkali until the pH value of the reaction system is 5-10.

[0055] Preferably, the graphitization agent comprises metal oxalate and / or metal citrate;

[0056] The metal includes one or more of nickel, magnesium, stannous, iron, zinc and manganese;

[0057] The carbonization temperature is 650-1300°C;

[0058] The carbonization time is 3 to 16 hours.

[0059] Preferably, the gaseous silicon source comprises monosilane;

[0060] The temperature of the silicon deposition is 300-980°C;

[0061] The silicon deposition time is 20 to 90 minutes.

[0062] Preferably, the C1-C4 low-carbon chain carbon source includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne and butyne;

[0063] The temperature of the carbon coating is 300-800°C;

[0064] The carbon coating time is 20min~4h.

[0065] The present invention provides a negative electrode plate, which includes the microporous carbon-silicon composite negative electrode material in the application described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material described in any one of the above technical solutions, or the microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of the above technical solutions.

[0066] The present invention provides a secondary battery, which comprises the microporous carbon-silicon composite negative electrode material in the application described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of the above technical solutions, or the negative electrode sheet described in the above technical solutions.

[0067] The present invention provides an application of nitrated lignin sulfonate in preparing a microporous carbon-silicon composite negative electrode material. Compared with the prior art, the present invention specifically uses nitrated lignin sulfonate in preparing a microporous carbon-silicon composite negative electrode material, and designs a microporous carbon-silicon composite negative electrode material with a specific structure and prepared by combining multiple carbon sources, which is a multi-phase doped silicon-carbon composite negative electrode material.

[0068] The microporous carbon-silicon composite negative electrode material provided by the present invention adopts carbonization of lignin-polymer interconnected composite to construct an interconnected carbon network structure, and further forms nano-graphitized carbon ribbons inside the carbon network structure, which, on the one hand, hinders the microphase separation between the two phases of lignin and phenolic resin polymer, so that the pore size of the obtained microporous carbon-silicon composite negative electrode material is more micropores within 2nm; on the other hand, the interconnected carbon network structure interconnects the pores of the nano-carbon material, and the silicon-carbon matrix is ​​more tightly combined. The sufficient and interconnected channel characteristics are conducive to reducing the diffusion resistance of lithium ions, optimizing the electron transmission path, improving the electron transmission efficiency, and facilitating lithium ions to enter the micropores and alloy with silicon to form a silicon-lithium phase. At the same time, the amorphous carbon protection zone formed by the low-carbon chain carbon source is protected from silicon cracking and crushing during the lithium ion embedding / ejection process; adding a graphitizing agent, catalyzing the amorphous carbon of the lignin-polymer interconnected mixture to form a nano-scale graphitized carbon ribbon, because amorphous carbon also has the problem of poor conductivity, and the graphite ribbon can provide an electron migration path, thereby improving the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material.

[0069] The present invention also provides a method for preparing a microporous carbon-silicon composite negative electrode material, which has simple process, mild conditions, strong controllability, good stability, and is more suitable for promotion and application in large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 This is a TEM image of the microporous carbon-silicon composite negative electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0071] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.

[0072] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0073] The raw materials used in the present invention involve products of specific brands, and there is no particular limitation on the source thereof. The products commercially available from conventional manufacturers of the brands well known to those skilled in the art can be used.

[0074] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity in the field of silicon-carbon composite negative electrode materials for lithium-ion secondary batteries.

[0075] The invention provides application of nitrated lignin sulfonate in preparing microporous carbon-silicon composite negative electrode material.

[0076] In the present invention, the application also preferably includes the application of combining nitrated lignin sulfonate and phenolic resin prepolymer in the preparation of microporous carbon-silicon composite negative electrode material.

[0077] In the present invention, the combination of the nitrated lignin sulfonate and the phenolic resin prepolymer is preferably such that the nitrated lignin sulfonate and the phenolic resin prepolymer are subjected to secondary polymerization to form a nitrated lignin-polymer composite.

[0078] In the present invention, the nitrated lignin-polymer composite preferably has a chemically bonded interpenetrating network structure.

[0079] In the present invention, the chemical bonding preferably comprises chemical bonding between the hydroxyl groups of the nitrated lignin sulfonate and the aldehyde groups in the prepolymer.

[0080] In the present invention, in the nitrated lignin-polymer composite, the network structure of the nitrated lignin sulfonate preferably interpenetrates with the network structure of the phenolic resin to form an interpenetrating network structure.

[0081] In the present invention, the mass ratio of the added amount of nitrated lignin to the phenolic resin prepolymer is preferably (0.002-0.08):1, more preferably (0.01-0.06):1, and more preferably (0.02-0.04):1.

[0082] In the present invention, the application also preferably includes the application of nitrated lignin sulfonate, phenolic resin prepolymer and graphitization agent in the preparation of microporous carbon-silicon composite negative electrode material.

[0083] In the present invention, the graphitization agent preferably includes metal oxalate and / or metal citrate, more preferably metal oxalate or metal citrate.

[0084] In the present invention, the mass ratio of the graphitization agent to the nitrated lignin-polymer composite is preferably (0.005-0.06):1, more preferably (0.01-0.05):1, and more preferably (0.02-0.04):1.

[0085] In the present invention, the application also preferably includes the application of nitrated lignin sulfonate, phenolic resin prepolymer, graphitization agent and C1~C4 low carbon chain carbon source in the preparation of microporous carbon-silicon composite negative electrode material.

[0086] In the present invention, the C1~C4 low-carbon chain carbon source preferably includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne and butyne, more preferably methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne or butyne.

[0087] In the present invention, the C1-C4 low-carbon chain carbon source is preferably used to form a coating layer of a microporous carbon-silicon composite negative electrode material.

[0088] In the present invention, the application is specifically preferably an application in reducing the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material and / or improving the discharge performance of the microporous carbon-silicon composite negative electrode material, and more preferably an application in reducing the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material and improving the discharge performance of the microporous carbon-silicon composite negative electrode material.

[0089] In the present invention, the micropores in the microporous carbon-silicon composite negative electrode material preferably satisfy the following relationship:

[0090] 0.22≤MP 2- / MP all ≤0.58;

[0091] Among them, MP 2- It is the total volume of micropores per unit mass in the microporous carbon-silicon composite negative electrode material; (“2-” represents less than 2nm)

[0092] MP all It is the total volume of pores per unit mass of microporous carbon-silicon composite negative electrode material.

[0093] In the present invention, preferably 0.22≤MP 2- / MP all ≤0.58, more preferably 0.3≤MP 2- / MP all ≤0.55, more preferably 0.35≤MP 2- / MP all ≤0.5.

[0094] In the present invention, the pore volume test method is specifically the following steps:

[0095] First pre-treat (treat at 200℃ for 2h to remove impurities such as air and water adsorbed by the negative electrode material), and use a specific surface area pore size analyzer under nitrogen / argon atmosphere, with a desorption temperature of 250℃ and a desorption pressure of <10Pa. Compare the measured nitrogen adsorption and desorption isotherms with the IUPAC classification, and use the density functional theory (DFT) method to obtain the adsorption / desorption relative pressure, adsorption amount, desorption amount and other data of the negative electrode material, and then calculate and fit to obtain the pore volume of the negative electrode material with a pore size of 0~2nm and the pore volume of all pore sizes. Among them, MP 2- The pore volume is less than 2nm.

[0096] The invention provides a microporous carbon-silicon composite negative electrode material. The microporous carbon-silicon composite negative electrode material is prepared from nitrated lignin sulfonate, phenolic resin prepolymer, a graphitization agent, a silicon source and a C1-C4 low-carbon chain carbon source.

[0097] In the present invention, the microporous carbon-silicon composite negative electrode material has a coating structure.

[0098] In the present invention, the coating structure is preferably that the surface of the microporous carbon-silicon composite negative electrode material has a carbon coating layer.

[0099] In the present invention, the thickness of the carbon coating layer is preferably 2-80 nm, more preferably 12-60 nm, and more preferably 30-40 nm.

[0100] In the present invention, the specific surface area of ​​the microporous carbon-silicon composite negative electrode material is preferably 0.75-8 m 2 / g, more preferably 0.9 to 6 m 2 / g, more preferably 1.2 to 3.5 m 2 / g.

[0101] In the present invention, the mass content of carbon in the microporous carbon-silicon composite negative electrode material is preferably 15% to 65%, more preferably 35% to 55%, and more preferably 40% to 50%.

[0102] In the present invention, the mass content of silicon in the microporous carbon-silicon composite negative electrode material is preferably 15% to 65%, more preferably 35% to 60%, and more preferably 40% to 55%.

[0103] In the present invention, the mass content of carbon and silicon in the microporous carbon-silicon composite negative electrode material is preferably 80% to 99%, more preferably 84% to 96%, and more preferably 90% to 95%.

[0104] In the present invention, the carbon main body of the microporous carbon-silicon composite negative electrode material is preferably porous carbon and nanographitized carbon ribbon formed by carbonization of nitrated lignin-polymer composite.

[0105] The present invention provides a method for preparing a microporous carbon-silicon composite negative electrode material, comprising the following steps:

[0106] 1) Prepolymerizing a phenol source, an aldehyde source and an acid catalyst, and then adding nitrated lignin sulfonate to perform secondary polymerization to obtain a nitrated lignin-polymer composite;

[0107] 2) Under vacuum conditions, the nitrated lignin-polymer composite obtained in the above step and the graphitization agent are heated, melted and mixed, and then carbonized under a protective atmosphere to obtain a nitrated lignin-polymer microporous carbon precursor;

[0108] 3) After acid washing, the nitrated lignin-polymer microporous carbon precursor obtained in the above step is introduced into a gaseous silicon source under vacuum conditions to perform silicon deposition to obtain a microporous carbon silicon matrix;

[0109] 4) Under the condition of a low-carbon chain carbon source of C1~C4, the microporous carbon silicon matrix obtained in the above steps is carbon-coated to obtain a microporous carbon silicon composite negative electrode material.

[0110] The invention firstly performs prepolymerization reaction on a phenol source, an aldehyde source and an acid catalyst, then adds nitrated lignin sulfonate to perform secondary polymerization to obtain a nitrated lignin-polymer composite.

[0111] In the present invention, the phenol source preferably includes one or more of phenol, nitrophenol, p-cresol, meta-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol and naphthalene, and more preferably includes phenol, nitrophenol, p-cresol, meta-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol or naphthalene.

[0112] In the present invention, the aldehyde source preferably includes one or more of formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde and furfural, more preferably formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde or furfural.

[0113] In the present invention, the acid catalyst preferably includes p-toluenesulfonic acid.

[0114] In the present invention, the amount of the phenol source and the aldehyde source, calculated as a phenol-aldehyde molar ratio, is preferably 1:(1.5-4), more preferably 1:(2-3.5), and more preferably 1:(2.5-3).

[0115] In the present invention, the temperature of the prepolymerization reaction is preferably 35-70°C, more preferably 40-65°C, more preferably 45-60°C, more preferably 50-55°C.

[0116] In the present invention, the prepolymerization reaction time is preferably 0.3 to 2 h, more preferably 0.7 to 1.6 h, and more preferably 1.1 to 1.2 h.

[0117] In the present invention, the temperature of the secondary polymerization is preferably 35-70°C, more preferably 40-65°C, more preferably 45-60°C, more preferably 50-55°C.

[0118] In the present invention, the secondary polymerization time is preferably 1 to 5 hours, more preferably 1.8 to 4.2 hours, and more preferably 2.6 to 3.4 hours.

[0119] In the present invention, the nitrated lignin-polymer composite obtained in the above steps and the graphitization agent are heated, melted and mixed under vacuum conditions, and then carbonized under a protective atmosphere to obtain a nitrated lignin-polymer microporous carbon precursor.

[0120] In the present invention, the preparation process of the nitrated lignin sulfonate preferably comprises the following steps:

[0121] After the lignin sulfonate solution and nitric acid are reacted, an alkali is added to obtain nitrated lignin.

[0122] In the present invention, the mass ratio of the lignin sulfonate to nitric acid is preferably 1:(0.1-0.8), more preferably 1:(0.25-0.65), and more preferably 1:(0.4-0.5).

[0123] In the present invention, the lignin sulfonate preferably includes one or more of sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate and magnesium lignin sulfonate, more preferably sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate or magnesium lignin sulfonate.

[0124] In the present invention, the reaction temperature is preferably 30-80°C, more preferably 40-70°C, and more preferably 50-60°C.

[0125] In the present invention, the reaction time is preferably 1 to 8 hours, more preferably 2.5 to 6.5 hours, and more preferably 4 to 5 hours.

[0126] In the present invention, the adding of alkali is preferably performed until the pH value of the reaction system is 5-10.

[0127] The present invention then acid-washes the nitrated lignin-polymer microporous carbon precursor obtained in the above steps, and then introduces a gaseous silicon source under vacuum conditions to perform silicon deposition to obtain a microporous carbon silicon matrix.

[0128] In the present invention, the graphitization agent preferably includes metal oxalate and / or metal citrate, more preferably metal oxalate or metal citrate.

[0129] In the present invention, the metal preferably includes one or more of nickel, magnesium, stannous, iron, zinc and manganese, and more preferably nickel, magnesium, stannous, iron, zinc or manganese.

[0130] In the present invention, the carbonization temperature is preferably 650-1300°C, more preferably 800-1150°C, and more preferably 950-1000°C.

[0131] In the present invention, the carbonization time is preferably 3 to 16 hours, more preferably 6 to 13 hours, and more preferably 9 to 10 hours.

[0132] In the present invention, the gaseous silicon source preferably includes monosilane.

[0133] In the present invention, the temperature of silicon deposition is preferably 300-980°C, more preferably 450-830°C, and more preferably 600-680°C.

[0134] In the present invention, the silicon deposition time is preferably 20 to 90 min, more preferably 35 to 75 min, and more preferably 50 to 60 min.

[0135] Finally, the present invention performs carbon coating on the microporous carbon silicon matrix obtained in the above steps under the condition of a low carbon chain carbon source of C1-C4 to obtain a microporous carbon silicon composite negative electrode material.

[0136] In the present invention, the C1~C4 low-carbon chain carbon source preferably includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne and butyne, more preferably methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne or butyne.

[0137] In the present invention, the temperature of the carbon coating is preferably 300-800°C, more preferably 400-700°C, and more preferably 500-600°C.

[0138] In the present invention, the carbon coating time is preferably 20 min to 4 h, more preferably 1 h to 3.5 h, more preferably 1.5 h to 3 h, more preferably 2 h to 2.5 h.

[0139] The present invention is to complete and refine the overall technical solution, better ensure the composition and specific structure of the microporous carbon-silicon composite negative electrode material, improve the discharge performance of the microporous carbon-silicon composite negative electrode material, and reduce the low-temperature discharge resistance of the material. The above-mentioned microporous carbon-silicon composite negative electrode material and its preparation method may specifically include the following contents:

[0140] A method for preparing a microporous carbon-silicon composite negative electrode material comprises the following steps:

[0141] (1) adding a phenol source and an aldehyde source to a reaction container, then adding p-toluenesulfonic acid, mixing evenly, and prepolymerizing to obtain a prepolymer, then adding 0.002-0.08 of the mass of the prepolymer nitrated lignin, mixing, and performing secondary polymerization to obtain a lignin-polymer interconnected mixture;

[0142] (2) sending the lignin-polymer interconnected mixture prepared in step (1) to a heating container, evacuating the container, adding a graphitizing agent, heating to a molten state, stirring and mixing, and then sending the mixture to a heating furnace to be filled with protective gas, carbonized, and crushed to obtain a lignin-polymer interconnected microporous carbon precursor;

[0143] (3) acid-washing and drying the microporous carbon precursor prepared in step (2), sending the dried microporous carbon precursor to a fluidized bed, introducing a protective gas to remove air, evacuating the deposition area inside the fluidized bed, introducing a silicon source, and depositing silicon on the microporous carbon precursor to obtain a microporous carbon silicon matrix;

[0144] (4) The microporous carbon silicon substrate prepared in step (3) is sent to a reaction furnace, and a low-carbon chain carbon source of C1 to C4 is introduced for coating to obtain a microporous carbon silicon composite negative electrode material.

[0145] Specifically, in step (1), the microporous carbon-silicon composite negative electrode material has micropores (pores with a pore size of <2 nm) and mesopores (pores with a pore size of 2-50 nm), and the volume of the micropores satisfies the following relationship:

[0146] 0.22≤MP 2- / MP all ≤0.58;

[0147] MP 2- It is the total volume of pores with a pore size of less than 2 nm per unit mass of microporous carbon-silicon composite negative electrode material;

[0148] MP all It is the total volume of pores per unit mass of microporous carbon-silicon composite negative electrode material.

[0149] Specifically, in step (1), the carbon main body of the microporous carbon-silicon composite negative electrode material is porous carbon and nanographitized carbon ribbon formed by carbonizing a lignin-polymer interconnected mixture.

[0150] Specifically, in step (1), the phenol source includes at least one of phenol, nitrophenol, p-quinone, m-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol, and naphthine.

[0151] The aldehyde source includes at least one of formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde and furfural.

[0152] The phenol source and the aldehyde source are mixed in a phenol-aldehyde molar ratio of 1:1.5-4.

[0153] Specifically, the preparation of the nitrated lignin in step (1) comprises: adding 1 part by weight of lignin sulfonate to 5-30 parts by weight of water to dissolve, then adding 0.1-0.8 parts by weight of nitric acid, reacting at 30-80° C. for 1-8 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 5-10, thereby obtaining nitrated lignin.

[0154] Specifically, the lignin sulfonate is at least one of sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate, and magnesium lignin sulfonate.

[0155] Specifically, the amount of nitrated lignin added is 0.002-0.08 of the mass of the prepolymer.

[0156] Specifically, in step (2), the graphitizing agent includes one or more of nickel / magnesium / stannous / iron / zinc / manganese in oxalic acid or citric acid.

[0157] Specifically, the graphitization agent is added in an amount of 0.005-0.06 of the lignin-polymer interconnected mixture.

[0158] Specifically, in step (2), the protective gas is one or more of nitrogen, helium, and argon.

[0159] Specifically, the carbonization temperature is 650-1300°C.

[0160] Specifically, the carbonization time is 3 to 16 hours.

[0161] Specifically, in step (4), the C1-C4 low-carbon chain carbon source includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne, and butyne.

[0162] The microporous carbon-silicon composite negative electrode material provided by the present invention is prepared by the preparation method described in any one of the above technical solutions.

[0163] Specifically, the microporous carbon-silicon composite negative electrode material has micropores (pores with a pore size of <2 nm) and mesopores (pores with a pore size of 2-50 nm), and the volume of the micropores satisfies the following relationship:

[0164] 0.22≤MP 2- / MP all ≤0.58.

[0165] Specifically, the carbon main body of the microporous carbon-silicon composite negative electrode material is porous carbon and nanographitized carbon ribbon formed by carbonizing a lignin-polymer interconnected mixture.

[0166] Specifically, the surface of the microporous carbon-silicon composite negative electrode material also has a carbon layer deposited from a low-carbon chain carbon source.

[0167] Specifically, the microporous carbon-silicon composite negative electrode material has a specific surface area of ​​0.75 to 8 m 2 / g.

[0168] Specifically, the carbon-silicon content in the microporous carbon-silicon composite negative electrode material satisfies: the carbon content is 15-65%, the silicon content is 15-65%, and the carbon content + silicon content satisfies 80-99%.

[0169] Furthermore, the method for preparing the microporous carbon-silicon composite negative electrode material of the present invention may include the following steps:

[0170] a. Lignin-polymer interconnected mixture: phenol source and aldehyde source are mixed and added into a reaction container, and then p-toluenesulfonic acid is added, mixed evenly, and prepolymerized to obtain a prepolymer, and then nitrated lignin is added, mixed, and secondary polymerization is performed to obtain a lignin-polymer interconnected mixture;

[0171] b. Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, a graphitizing agent is added, heated to a molten state, stirred and mixed, and then sent to a heating furnace to be filled with protective gas, carbonized, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor;

[0172] c. Deposition: The microporous carbon precursor is acid-washed and dried, and the dried microporous carbon precursor is sent to a fluidized bed, and a protective gas is introduced to remove the air. The deposition area inside the fluidized bed is evacuated, and a silicon source is introduced. The microporous carbon precursor is subjected to silicon deposition to obtain a microporous carbon silicon matrix;

[0173] d. Carbon source coating: The microporous carbon silicon substrate is sent to a reactor, and a low-carbon chain carbon source of C1~C4 is introduced for coating to obtain a microporous carbon silicon composite negative electrode material.

[0174] Furthermore, in step a, the phenol source includes at least one of phenol, nitrophenol, p-quinone, m-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol, and naphthine.

[0175] Furthermore, in step a, the aldehyde source includes at least one of formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde and furfural.

[0176] Furthermore, in step a, the phenol source and the aldehyde source are mixed in a phenol-aldehyde molar ratio of 1:1.5-4.

[0177] Furthermore, in step a, the amount of p-toluenesulfonic acid added is 0.05-0.9% of the total weight of the phenol source and the aldehyde source.

[0178] Furthermore, in step a, the prepolymer is a polymer in which the phenol source and the aldehyde source are not completely polymerized to form a phenolic resin polymer.

[0179] Furthermore, in step a, the prepolymerization temperature is 35-70° C. and the time is 0.3-2 h.

[0180] Furthermore, in step a, the secondary polymerization temperature is 35-70° C. and the time is 1-5 hours.

[0181] Furthermore, in step a, the amount of nitrated lignin added is 0.002-0.08 of the mass of the prepolymer.

[0182] Furthermore, in step a, the preparation of the nitrated lignin includes: adding 1 part by weight of lignin sulfonate to 5-30 parts by weight of water to dissolve, then adding 0.1-0.8 parts by weight of nitric acid, reacting at 30-80° C. for 1-8 hours, and after the reaction is complete, adding ammonia water dropwise until the pH is 5-10, which is the nitrated lignin;

[0183] Furthermore, the lignin sulfonate is at least one of sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate, and magnesium lignin sulfonate.

[0184] Furthermore, in step a, the lignin-polymer interconnected mixture: the nitrated lignin sulfonate is rich in a polyhydroxy network structure, and the addition of nitrated lignin causes the prepolymer to be complexed and interconnected by the nitrated lignin, and after polymerization, they are internally interconnected to form a lignin-polymer interconnected mixture.

[0185] Furthermore, in step b, the graphitizing agent includes one or more of nickel / magnesium / stannous / iron / zinc / manganese in oxalic acid or citric acid.

[0186] Furthermore, in step b, the amount of the graphitization agent added ranges from 0.005 to 0.06 of the lignin-polymer interconnected mixture.

[0187] Furthermore, in step b, after adding the graphitizing agent, the mixture is heated to a molten state at 85-180°C.

[0188] Furthermore, in step b, the protective gas is one or more of nitrogen, helium, and argon.

[0189] Furthermore, in step b, the carbonization temperature is 650-1300° C., and the carbonization time is 3-16 hours.

[0190] Furthermore, in step b, the particle size of the lignin-polymer interconnected microporous carbon precursor obtained after the crushing is 2.0-200 μm.

[0191] Furthermore, in step c, the acid washing is performed by adding the microporous carbon precursor into a hydrochloric acid solution (hydrogen chloride content 0.5-12 wt%) with a mass of 5-20 times the mass of the microporous carbon precursor, shaking, and filtering 3-8 times.

[0192] Furthermore, in step c, after pickling, the product is dried at 95-150°C.

[0193] Furthermore, in step c, the temperature of the fluidized bed is controlled at 300-980°C.

[0194] Furthermore, in step c, the microporous carbon precursor is subjected to silicon deposition for 20 to 90 minutes.

[0195] Furthermore, in step c, silicon in the microporous carbon precursor is deposited to a silicon content of 15-65%.

[0196] Furthermore, in step d, the temperature of the reaction furnace is controlled at 300-800°C.

[0197] Furthermore, in step d, the C1-C4 low-carbon chain carbon source includes one or more of methane, ethane, propane, butane, butene, ethylene, ethylenediene, butene, butadiene, acetylene, propyne, and butyne.

[0198] Furthermore, in step d, the coating time is 20 min to 4 h.

[0199] The present invention provides a negative electrode plate, which includes the microporous carbon-silicon composite negative electrode material in the application described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material described in any one of the above technical solutions, or the microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of the above technical solutions.

[0200] The present invention is to complete and refine the overall technical solution, better ensure the composition and specific structure of the microporous carbon-silicon composite negative electrode material, improve the discharge performance of the microporous carbon-silicon composite negative electrode material, and reduce the low-temperature discharge resistance of the material. The preparation method of the above-mentioned negative electrode sheet can specifically include the following contents:

[0201] (1) weighing a microporous carbon-silicon composite negative electrode material, a graphite negative electrode material, a conductive material and a binding material, and stirring and mixing the microporous carbon-silicon composite negative electrode material with a portion of the conductive material, a portion of the binding material and water for the first time to obtain a primary mixture;

[0202] (2) the primary mixture prepared in step (1) is stirred and mixed for a second time with the remaining conductive material, the remaining adhesive material, and water to obtain a total mixture, wherein the total mixture has a solid matter content of 40-65% and a viscosity of 1000-8000 mPa·s;

[0203] (3) The total mixed material prepared in step (2) is coated on the negative electrode fluid, and after drying and pressing, the negative electrode sheet is obtained.

[0204] The present invention provides a secondary battery, which comprises the microporous carbon-silicon composite negative electrode material in the application described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material described in any one of the above technical solutions, the microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of the above technical solutions, or the negative electrode sheet described in the above technical solutions.

[0205] The present invention is to complete and refine the overall technical solution, better ensure the composition and specific structure of the microporous carbon-silicon composite negative electrode material, improve the discharge performance of the microporous carbon-silicon composite negative electrode material, and reduce the low-temperature discharge resistance of the material. The above-mentioned secondary battery, that is, the application of the negative electrode sheet on the secondary battery, the specific preparation method or application method may include the following contents:

[0206] (1) weighing a microporous carbon-silicon composite negative electrode material, a graphite negative electrode material, a conductive material and a binding material, and stirring and mixing the microporous carbon-silicon composite negative electrode material with a portion of the conductive material, a portion of the binding material and water for the first time to obtain a primary mixture;

[0207] (2) the primary mixture prepared in step (1) is stirred and mixed for a second time with the remaining conductive material, the remaining adhesive material, and water to obtain a total mixture, wherein the total mixture has a solid matter content of 40-65% and a viscosity of 1000-8000 mPa·s;

[0208] (3) coating the total mixed material prepared in step (2) on the negative electrode fluid, drying, cold pressing, and cutting to obtain the negative electrode sheet;

[0209] (4) The negative electrode sheet, separator, and positive electrode sheet prepared in step (3) are stacked, wound, ultrasonically welded, and glued to obtain a bare cell. The bare cell is placed in a battery case, dried at 150-185° C. to remove moisture, and an electrolyte is injected into the battery case and packaged to obtain a secondary battery.

[0210] Specifically, in step (1), the graphite negative electrode material is selected from at least one of coal-based needle coke, petroleum-based needle coke, or a graphite negative electrode material obtained by mixing, crushing, and graphitizing petroleum coke and asphalt, and a graphite negative electrode material obtained by coating and modifying natural graphite.

[0211] Specifically, in step (1), the conductive material is at least one of conductive carbon black, acetylene black, graphite, graphene, carbon microwires, carbon nanowires, single-walled carbon microtubes, multi-walled carbon microtubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0212] Specifically, in step (1), the bonding material is polyacrylonitrile, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, polyacrylate, styrene-butadiene rubber, or sodium alginate.

[0213] Specifically, in step (2), the solid matter content in the total mixture is more preferably 45-55%, and the viscosity is more preferably 2600-3800 mPa·s.

[0214] Specifically, in step (2), the mass ratio of the total mass of the microporous carbon-silicon composite negative electrode material and the graphite negative electrode material to the mass ratio of the conductive material and the bonding material in the total mixture is: 85-99.5: 0.1-7: 0.2-8.

[0215] Specifically, the ratio of the microporous carbon-silicon composite negative electrode material and the graphite negative electrode material is (0.2-9): (1-9.8), for example, it can be 0.2:9.8, 0.5:9.5, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, etc.

[0216] The above content of the present invention provides the application of nitrated lignin sulfonate in the preparation of microporous carbon-silicon composite negative electrode materials, a microporous carbon-silicon composite negative electrode material and its preparation method, a negative electrode plate, and a secondary battery. The present invention particularly uses nitrated lignin sulfonate in the preparation of microporous carbon-silicon composite negative electrode materials, and designs a microporous carbon-silicon composite negative electrode material with a specific structure and a combination of multiple carbon sources, which is a multi-phase doped silicon-carbon composite negative electrode material. The microporous carbon-silicon composite negative electrode material provided by the present invention uses lignin-polymer interconnected composite carbonization to construct an interconnected carbon network structure, and further forms nanographitized carbon ribbons inside the carbon network structure. On the one hand, it hinders the microphase separation between the two phases of lignin and phenolic resin polymer, so that the pore size of the obtained microporous carbon-silicon composite negative electrode material forms micropores within 2nm; on the other hand, the interconnected carbon network structure interconnects the pores of the nanocarbon material, and the silicon-carbon matrix is ​​more tightly combined. The sufficient and interconnected channel characteristics are conducive to reducing the diffusion resistance of lithium ions, optimizing the electron transmission path, and improving the electron transmission efficiency, and it is conducive to lithium ions entering the micropores and alloying with silicon to form silicon-lithium phases. At the same time, the amorphous carbon protection zone formed by the low-carbon chain carbon source is protected from silicon cracking and crushing during the lithium ion insertion / extraction process; the addition of graphitization reagents catalyzes the formation of nano-scale graphitized carbon ribbons from the interconnected lignin-polymer mixture amorphous carbon. Since amorphous carbon also has the problem of poor conductivity, the graphite ribbon can provide an electron migration pathway, thereby improving the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material.

[0217] The present invention also provides a method for preparing a microporous carbon-silicon composite negative electrode material, which has simple process, mild conditions, strong controllability, good stability, and is more suitable for promotion and application in large-scale industrial production.

[0218] In order to further illustrate the present invention, the application of the nitrated lignin sulfonate provided by the present invention in the preparation of a microporous carbon-silicon composite negative electrode material, a microporous carbon-silicon composite negative electrode material and a preparation method thereof, a negative electrode plate, and a secondary battery are described in detail in combination with the embodiments below. However, it should be understood that these embodiments are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the present invention, and the protection scope of the present invention is not limited to the following embodiments. Example 1

[0219] 1. Preparation method of microporous carbon-silicon composite negative electrode material:

[0220] a Lignin-polymer interconnected mixture: phenol source (p-benzol) and aldehyde source (paraformaldehyde) (phenol-aldehyde molar ratio of 1:3.5) are mixed and added into a reaction container, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.2% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 45°C for 0.75h to obtain a prepolymer, and then 0.005 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (45°C for 4h) is performed to obtain a lignin-polymer interconnected mixture;

[0221] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 15 parts by mass of water to dissolve, then adding 0.24 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.3, which is nitrated lignin.

[0222] b. Carbonization of lignin-polymer interconnected mixture: the lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.008 nickel oxalate of the lignin-polymer interconnected mixture is added, heated to a molten state of 145°C, stirred and mixed, and then sent to a heating furnace filled with nitrogen, carbonized at 900°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor;

[0223] c Deposition: The microporous carbon precursor is added to a hydrochloric acid solution (hydrogen chloride content 4wt%) with a mass of 10 times the mass thereof, shaken, filtered 5 times, and dried at 105°C. The dried microporous carbon precursor is sent to a fluidized bed, and a protective gas is introduced to remove the air. The deposition area inside the fluidized bed is evacuated, and the temperature of the fluidized bed is controlled at 580°C. Monosilane is introduced, and silicon is deposited on the microporous carbon precursor for 45 minutes. The silicon in the microporous carbon precursor is deposited to a silicon content of 48%, thereby obtaining a microporous carbon silicon matrix;

[0224] d Carbon source coating: The microporous carbon silicon substrate is sent to a reactor, the temperature of the reactor is controlled at 500°C, acetylene is introduced, and the coating is carried out for 1 hour to obtain a microporous carbon silicon composite negative electrode material.

[0225] 2. Application in secondary batteries

[0226] (1) Weighing microporous carbon silicon composite negative electrode material + graphite negative electrode material obtained by graphitization of needle coke (microporous carbon silicon composite negative electrode material and graphite negative electrode material are composed of 1:9), conductive material (composed of 9 parts of conductive carbon black and 1 part of single-walled carbon microtubes) and binding material (composed of 1 part of sodium carboxymethyl cellulose and 2 parts of lithium acrylate), stirring and mixing the microporous carbon silicon composite negative electrode material with part of the conductive material, part of the binding material and water for the first time to obtain a primary mixture;

[0227] (2) The primary mixture prepared in step (1) is stirred and mixed for a second time with the remaining conductive material, the remaining binding material, and water to obtain a total mixture (the mass ratio of the total mass of the microporous carbon-silicon composite negative electrode material and the graphite negative electrode material to the conductive material and the binding material is 96:1.5:2), wherein the solid content of the total mixture is 49% and the viscosity is 2900 mPa·s;

[0228] (3) coating the total mixed material prepared in step (2) on the negative electrode fluid, drying, cold pressing, and cutting to obtain the negative electrode sheet;

[0229] (4) The negative electrode sheet, separator, and positive electrode sheet (containing 97.5wt% lithium nickel cobalt manganese oxide LiNi) prepared in step (3) are placed in a 0.63 Co 0.12 Mn 0.25 The negative electrode tabs and the positive electrode tabs are stacked and wound, and the separator is fixed with glue to obtain a bare cell. The bare cell is placed in an aluminum-plastic film with heat-sealed sides, dried at 105°C to remove moisture, 1.2 mol / L LiPF6 electrolyte is injected into the aluminum-plastic film, and the top is heat-sealed to obtain a 3.5Ah secondary battery. Example 2

[0230] The difference from Example 1 is:

[0231] a Lignin-polymer interconnected mixture: phenol source (p-benzol) and aldehyde source (paraformaldehyde) (at a phenol-aldehyde molar ratio of 1:3.5) are mixed and added into a reaction vessel, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.2% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 45°C for 0.75h to obtain a prepolymer, and then 0.008 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (45°C for 4h) is performed to obtain a lignin-polymer interconnected mixture;

[0232] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 15 parts by mass of water to dissolve, then adding 0.24 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.2, which is nitrated lignin.

[0233] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.008 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 145°C, stirred and mixed, and then sent to a heating furnace and filled with nitrogen, carbonized at 900°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor. Example 3

[0234] The difference from Example 1 is:

[0235] a Lignin-polymer interconnected mixture: phenol source (p-benzol) and aldehyde source (paraformaldehyde) (at a phenol-aldehyde molar ratio of 1:3.5) are mixed and added into a reaction vessel, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.2% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 45°C for 0.75h to obtain a prepolymer, and then 0.012 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (45°C for 4h) is performed to obtain a lignin-polymer interconnected mixture;

[0236] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 15 parts by mass of water to dissolve, then adding 0.24 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.5, which is nitrated lignin.

[0237] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.008 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 145°C, stirred and mixed, and then sent to a heating furnace and filled with nitrogen, carbonized at 900°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor. Example 4

[0238] The difference from Example 1 is:

[0239] a Lignin-polymer interconnected mixture: phenol source (p-benzol) and aldehyde source (paraformaldehyde) (phenol-aldehyde molar ratio of 1:3.5) are mixed and added into a reaction vessel, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.75% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 45°C for 0.75h to obtain a prepolymer, and then 0.015 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (45°C for 4h) is performed to obtain a lignin-polymer interconnected mixture;

[0240] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 15 parts by mass of water to dissolve, then adding 0.24 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.8, which is nitrated lignin.

[0241] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.008 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 145°C, stirred and mixed, and then sent to a heating furnace and filled with nitrogen, carbonized at 900°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor.

[0242] See also Figure 1 , Figure 1 This is a TEM image of the microporous carbon-silicon composite negative electrode material prepared in Example 4 of the present invention, wherein the dark area is the nanographitized carbon ribbon. Example 5

[0243] 1. Preparation method of microporous carbon-silicon composite negative electrode material:

[0244] a Lignin-polymer interconnected mixture: phenol source (phenol) and aldehyde source (paraformaldehyde) (according to the phenol-aldehyde molar ratio of 1:3.3) are mixed and added into a reaction container, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.45% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 50°C for 0.75h to obtain a prepolymer, and then 0.005 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (50°C, time is 4h) is carried out to obtain a lignin-polymer interconnected mixture;

[0245] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 19 parts by mass of water to dissolve, then adding 0.2 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.4, which is nitrated lignin.

[0246] b. Carbonization of lignin-polymer interconnected mixture: the lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.01 stannous oxalate of the lignin-polymer interconnected mixture is added, heated to a molten state of 160°C, stirred and mixed, and then sent to a heating furnace filled with nitrogen, carbonized at 900°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor;

[0247] c Deposition: The microporous carbon precursor is added to a hydrochloric acid solution (hydrogen chloride content 4wt%) with a mass of 10 times the mass thereof, shaken, filtered 5 times, and dried at 105°C. The dried microporous carbon precursor is sent to a fluidized bed, and a protective gas is introduced to remove the air. The deposition area inside the fluidized bed is evacuated, and the temperature of the fluidized bed is controlled at 640°C. Monosilane is introduced, and silicon is deposited on the microporous carbon precursor for 68 minutes. The silicon in the microporous carbon precursor is deposited to a silicon content of 55%, thereby obtaining a microporous carbon silicon matrix;

[0248] d Carbon source coating: The microporous carbon silicon substrate is sent to a reactor, the temperature of the reactor is controlled at 550°C, acetylene is introduced, and the coating is carried out for 50 minutes to obtain a microporous carbon silicon composite negative electrode material.

[0249] 2. Application in secondary batteries

[0250] (1) Weighing microporous carbon silicon composite negative electrode material + graphite negative electrode material obtained by graphitization of needle coke (microporous carbon silicon composite negative electrode material and graphite negative electrode material are composed of 1.5:8.5), conductive material (composed of 8 parts of conductive carbon black and 2 parts of single-walled carbon microtubes) and binding material (composed of 1 part of sodium carboxymethyl cellulose and 2 parts of lithium acrylate), stirring and mixing the microporous carbon silicon composite negative electrode material with part of the conductive material, part of the binding material and water for the first time to obtain a primary mixture;

[0251] (2) The primary mixture prepared in step (1) is stirred and mixed for a second time with the remaining conductive material, the remaining binding material, and water to obtain a total mixture (the mass ratio of the total mass of the microporous carbon-silicon composite negative electrode material and the graphite negative electrode material to the conductive material and the binding material is 95.5:1.8:2.7), wherein the solid content of the total mixture is 51% and the viscosity is 3500 mPa·s;

[0252] (3) coating the total mixed material prepared in step (2) on the negative electrode fluid, drying, cold pressing, and cutting to obtain the negative electrode sheet;

[0253] (4) The negative electrode sheet, separator, and positive electrode sheet (containing 97.5wt% lithium nickel cobalt manganese oxide LiNi) prepared in step (3) are placed in a 0.63 Co 0.12 Mn 0.25 The negative electrode tabs and the positive electrode tabs are stacked and wound, and the separator is fixed with glue to obtain a bare cell. The bare cell is placed in an aluminum-plastic film with heat-sealed sides, dried at 105°C to remove moisture, 1.2 mol / L LiPF6 electrolyte is injected into the aluminum-plastic film, and the top is heat-sealed to obtain a 3.5Ah secondary battery. Example 6

[0254] The difference from Example 5 is:

[0255] a Lignin-polymer interconnected mixture: phenol source (phenol) and aldehyde source (paraformaldehyde) (phenol-aldehyde molar ratio of 1:3.3) are mixed and added into a reaction container, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.45% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 50°C for 0.75h to obtain a prepolymer, and then 0.008 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (50°C, time is 4h) is carried out to obtain a lignin-polymer interconnected mixture;

[0256] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 19 parts by mass of water to dissolve, then adding 0.2 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.8, which is nitrated lignin.

[0257] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.01 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 160°C, stirred and mixed, and then sent to a heating furnace, filled with nitrogen, carbonized at 1050°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor. Example 7

[0258] The difference from Example 5 is:

[0259] a Lignin-polymer interconnected mixture: phenol source (phenol) and aldehyde source (paraformaldehyde) (phenol-aldehyde molar ratio of 1:3.3) are mixed and added into a reaction container, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.45% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 50°C for 0.75h to obtain a prepolymer, and then 0.012 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (50°C, time is 4h) is carried out to obtain a lignin-polymer interconnected mixture;

[0260] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 15 parts by mass of water to dissolve, then adding 0.2 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.4, which is nitrated lignin.

[0261] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.01 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 85-180°C, stirred and mixed, and then sent to a heating furnace and filled with nitrogen, carbonized at 1050°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor. Example 8

[0262] The difference from Example 5 is:

[0263] a Lignin-polymer interconnected mixture: phenol source (phenol) and aldehyde source (paraformaldehyde) (according to the phenol-aldehyde molar ratio of 1:3.3) are mixed and added into a reaction container, and then p-toluenesulfonic acid is added (the amount of p-toluenesulfonic acid added is 0.45% of the total weight of the phenol source and the aldehyde source), mixed evenly, and prepolymerized at 50°C for 0.75h to obtain a prepolymer, and then 0.015 of the mass of the prepolymer nitrated lignin is added, mixed, and secondary polymerization (50°C, time is 4h) is carried out to obtain a lignin-polymer interconnected mixture;

[0264] The preparation of nitrated lignin includes: adding 1 part by mass of sodium lignin sulfonate to 10 parts by mass of water to dissolve, then adding 0.2 parts by mass of nitric acid, reacting at 65°C for 4 hours, and after the reaction is completed, adding ammonia water dropwise until the pH is 7.6, which is nitrated lignin.

[0265] b Carbonization of lignin-polymer interconnected mixture: The lignin-polymer interconnected mixture is sent to a heating container, evacuated, 0.01 nickel oxalate is added to the lignin-polymer interconnected mixture, heated to a molten state of 160°C, stirred and mixed, and then sent to a heating furnace and filled with nitrogen, carbonized at 1050°C for 6h, crushed, and demagnetized to obtain a lignin-polymer interconnected microporous carbon precursor. Comparative Example 1

[0266] The difference from Example 1 is that in step (1), no nitrated lignin is added during prepolymerization, and the polymerization is directly carried out at 45° C. for 4.75 h. Comparative Example 2

[0267] The difference from Example 1 is that in step (2), no 0.008 nickel oxalate is added to the lignin-polymer interconnected mixture.

[0268] test:

[0269] (1) The powder resistance of the negative electrode material obtained in step d of Examples 1 to 8 and the powder resistance of the negative electrode material obtained in step d of Comparative Examples 1 to 2 were tested using a four-probe method of a powder resistance test system (test conditions: pressure 180 MPa, room temperature). See Table 1.

[0270] (2) Formation: The secondary batteries of Examples 1-8 and Comparative Examples 1-2 were first charged at 45°C with a current of 0.175 A to a voltage of 3.7 V, left to stand for 24 h, and then charged at a current of 1.75 A to a voltage of 4.3 V (4.3 V constant voltage charging current <0.175 A).

[0271] (3) Electrochemical test system test: ① At room temperature of 25°C, discharge at 3.5A for 30 minutes to obtain a secondary battery with 50% SOC, and discharge for 48 minutes to obtain a secondary battery with 20% SOC; ② Send the secondary batteries with 50% SOC and 20% SOC to a -20°C environment, let stand for 15 minutes (to ensure that the battery core reaches the thermal balance of -20°C), and then discharge at a constant current of 1.155A for 30 seconds, record the voltage before and after discharge, let stand for 5 minutes, and calculate the DCR of 50% SOC and 20% SOC for 30 seconds of Examples 1 to 8 and Comparative Examples 1 to 2 (DCR = voltage difference before and after discharge / 1.155A). As shown in Table 2.

[0272] (4) Pre-treatment (treatment at 200℃ for 2h to remove impurities such as air and water adsorbed by the negative electrode material), using a specific surface area pore size analyzer, under nitrogen / argon atmosphere, the desorption temperature is 250℃, and the desorption pressure is less than 10Pa. The measured nitrogen adsorption and desorption isotherm curve is compared with the IUPAC classification, and the density functional theory (DFT) method is used to obtain the adsorption / desorption relative pressure, adsorption amount, desorption amount and other data of the negative electrode material, and then the pore volume of the pore size of 0~2nm and the pore volume of all pore sizes of the negative electrode material are calculated and fitted. Among them, MP 2- The pore volume is less than 2nm, MP all is the total volume of pores per unit mass of microporous carbon-silicon composite negative electrode material, as shown in Table 3.

[0273]

[0274]

[0275]

[0276] In Tables 1 to 3, no nitrated lignin was added during the prepolymerization of the negative electrode material of Comparative Example 1, and the carbonization of the lignin-polymer interconnected composite constructed an interconnected carbon network structure with a lower proportion of 2nm micropores. In addition, the discharge DCR at -20°C was higher; in step (2) of Comparative Example 2, no 0.008 nickel oxalate of the lignin-polymer interconnected mixture was added, and the powder resistance and low-temperature discharge DCR were the highest. In Examples 1-8, the carbonization of the lignin-polymer interconnected composite constructed an interconnected carbon network structure, and the interconnected carbon network structure interconnected the pores of the nano-carbon material, and the silicon-carbon matrix was more tightly bonded, and the nano-scale graphitized carbon ribbons formed inside, the sufficient and interconnected channel characteristics were conducive to reducing the diffusion resistance of lithium ions, optimizing the electron transmission path, and thus improving the low-temperature discharge resistance of the microporous carbon-silicon composite negative electrode material. Therefore, the powder resistance of each group was lower than that of the comparative example; the 20% SOC discharge DCR and 50% SOC discharge DCR at -20°C were lower.

[0277] The above is a detailed introduction to the application of nitrated lignin sulfonate in the preparation of microporous carbon-silicon composite negative electrode materials, a microporous carbon-silicon composite negative electrode material and its preparation method, a negative electrode plate, and a secondary battery provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the present invention. The scope of patent protection of the present invention is limited and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the textual expression of the protection scope, or if they include equivalent structural elements that are not substantially different from the textual expression of the protection scope, then these other embodiments should also be included in the scope of protection.

Claims

1. A method for preparing a microporous carbon-silicon composite negative electrode material, characterized in that: The following steps are involved: 1) Prepolymerizing a phenol source, an aldehyde source and an acid catalyst, and then adding nitrated lignin sulfonate to perform secondary polymerization to obtain a nitrated lignin-polymer composite; The acid catalyst includes p-toluenesulfonic acid; The prepolymerization reaction time is 0.3 to 2 hours; The temperature of the prepolymerization reaction is 35-70°C; The secondary polymerization time is 1 to 5 hours; The temperature of the secondary polymerization is 35-70°C; 2) Under vacuum conditions, the nitrated lignin-polymer composite obtained in the above step and the graphitization agent are heated, melted and mixed, and then carbonized under a protective atmosphere to obtain a nitrated lignin-polymer microporous carbon precursor; The graphitization agent includes metal oxalate and / or metal citrate; The metal includes one or more of nickel, magnesium, stannous, iron, zinc and manganese; The carbonization temperature is 650-1300°C; The carbonization time is 3 to 16 hours; 3) After acid washing, the obtained nitrated lignin-polymer microporous carbon precursor is introduced into a gaseous silicon source under vacuum conditions to perform silicon deposition to obtain a microporous carbon silicon matrix; 4) Under the condition of a low-carbon chain carbon source of C1~C4, the obtained microporous carbon silicon matrix is ​​carbon-coated to obtain a microporous carbon silicon composite negative electrode material.

2. The preparation method according to claim 1, characterized in that: The phenol source includes one or more of phenol, nitrophenol, p-cresol, m-cresol, o-cresol, xylenol, hydroquinone, resorcinol, catechol and naphthol; The aldehyde source includes one or more of formaldehyde, acetaldehyde, glyoxal, paraformaldehyde, benzaldehyde, terephthalaldehyde and furfural.

3. The preparation method according to claim 1, characterized in that: The preparation process of the nitrated lignin sulfonate comprises the following steps: After the lignin sulfonate solution and nitric acid are reacted, an alkali is added to obtain nitrated lignin sulfonate.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the lignin sulfonate to nitric acid is 1:(0.1-0.8); The lignin sulfonate includes one or more of sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, lithium lignin sulfonate and magnesium lignin sulfonate; The reaction temperature is 30-80°C; The reaction time is 1 to 8 hours; The adding of alkali specifically includes adding alkali until the pH value of the reaction system is 5-10.

5. The preparation method according to claim 1, characterized in that: The gaseous silicon source includes monosilane; The temperature of the silicon deposition is 300-980°C; The silicon deposition time is 20 to 90 minutes.

6. The preparation method according to claim 1, characterized in that: The C1-C4 low-carbon chain carbon source includes one or more of methane, ethane, propane, butane, ethylene, ethylenediene, butylene, butadiene, acetylene, propyne and butyne; The temperature of the carbon coating is 300-800°C; The carbon coating time is 20min~4h.

7. The preparation method according to claim 1, characterized in that: The nitrated lignin-polymer composite has a chemically bonded interpenetrating network structure.

8. The preparation method according to claim 7, characterized in that: The chemical bonding includes chemical bonding between the hydroxyl group of the nitrated lignin sulfonate and the aldehyde group in the prepolymer.

9. The preparation method according to claim 7, characterized in that: In the nitrated lignin-polymer composite, the network structure of the nitrated lignin sulfonate and the network structure of the phenolic resin interpenetrate with each other to form an interpenetrating network structure; The C1-C4 low-carbon chain carbon source is used to form a coating layer of a microporous carbon-silicon composite negative electrode material.

10. A microporous carbon-silicon composite negative electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The microporous carbon-silicon composite negative electrode material has a coating structure.

11. The microporous carbon-silicon composite negative electrode material according to claim 10, characterized in that: The micropores in the microporous carbon-silicon composite negative electrode material satisfy the following relationship: 0.22≤MP 2- / MP all ≤0.58; in, MP 2- is the total volume of micropores per unit mass in the microporous carbon-silicon composite negative electrode material; MP all It is the total volume of pores per unit mass of microporous carbon-silicon composite negative electrode material.

12. The microporous carbon-silicon composite negative electrode material according to claim 10, characterized in that: The coating structure is specifically that the surface of the microporous carbon-silicon composite negative electrode material has a carbon coating layer; The thickness of the carbon coating layer is 2-80 nm; The specific surface area of ​​the microporous carbon-silicon composite negative electrode material is 0.75-8m 2 / g.

13. The microporous carbon-silicon composite negative electrode material according to claim 10, characterized in that: The mass content of carbon in the microporous carbon-silicon composite negative electrode material is 15% to 65%; The mass content of silicon in the microporous carbon-silicon composite negative electrode material is 15% to 65%; The mass content of carbon and silicon in the microporous carbon-silicon composite negative electrode material is 80% to 99%.

14. The microporous carbon-silicon composite negative electrode material according to claim 10, characterized in that: The carbon main body of the microporous carbon-silicon composite negative electrode material is porous carbon and nanographitized carbon ribbon formed by carbonizing a nitrated lignin-polymer composite.

15. A negative electrode plate, characterized in that: The negative electrode plate comprises a microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of claims 1 to 9 or a microporous carbon-silicon composite negative electrode material described in any one of claims 10 to 14.

16. A secondary battery, characterized in that: The secondary battery comprises the microporous carbon-silicon composite negative electrode material prepared by the preparation method described in any one of claims 1 to 9, the microporous carbon-silicon composite negative electrode material described in any one of claims 10 to 14, or the negative electrode sheet described in claim 15.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material, preparation method of material, and lithium ion battery

    CN110021737A

  • Porous silicon carbon negative electrode material and preparation method and application thereof

    CN117038941A

Cited By

  • Preparation method and application of sulfur-doped carbon-coated silicon-carbon negative electrode material

    CN121726361A